Jahves kamp med dragen; om baggrunden for kampmotivet i de gammeltestamentlige skabelsesforestillinger - Grønbæk, Jakob H. (1984)
Yahweh's Battie with the Dragon: On the Background of the Battle Theme in the Concepts of Creation in the Old Testament.